Modelling granules size distribution produced on a continuous manufacturating line with non-linear autoregressive artificial neural networks - Nunes, Diana Catherina Manaig (2019)
Tese de mestrado, Engenharia Farmacêutica, Universidade de Lisboa, Faculdade de Farmácia, 2018